2018
DOI: 10.1021/acs.organomet.8b00793
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Cp2Ti(H)Cl and Its Enigmatic Role in the Reactions of Epoxides with Cp2TiCl

Abstract: The role of Cp2Ti(H)Cl in the reactions of Cp2TiCl with trisubstituted epoxides has been investigated in a combined experimental and computational study. Although Cp2Ti(H)Cl has generally been regarded as a robust species, its decomposition to Cp2TiCl and molecular hydrogen was found to be exothermic (ΔG = −11 kcal/mol when the effects of THF solvation are considered). In laboratory studies, Cp2Ti(H)Cl was generated using the reaction of 1,2-epoxy-1-methylcyclohexane with Cp2TiCl as a model. Rapid evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 66 publications
(134 reference statements)
1
22
1
Order By: Relevance
“…The second equivalent of Cp 2 TiCl would be unnecessary, since half of the reagent would be converted into Cp 2 Ti(H)Cl, which then decomposes, regenerating Cp 2 TiCl. We demonstrated this in the laboratory [16] …”
Section: Mystery 1: the Case Of The Vanishing Intermediatementioning
confidence: 78%
See 2 more Smart Citations
“…The second equivalent of Cp 2 TiCl would be unnecessary, since half of the reagent would be converted into Cp 2 Ti(H)Cl, which then decomposes, regenerating Cp 2 TiCl. We demonstrated this in the laboratory [16] …”
Section: Mystery 1: the Case Of The Vanishing Intermediatementioning
confidence: 78%
“…Theplot thickens!Details of the calculations have been published elsewhere. [16] At this point, we could not resist going into the lab to have ah ands-on look at this chemistry.O ne of our collaborators, Kendra Dewese prepared the simple model epoxide 11 and added it to asolution of Cp 2 TiCl in THF.During the addition, she observed vigorous gas evolution!T he gas was confirmed to be hydrogen by GC-MS.Even better,using agas burette it was possible to the measure the amount of hydrogen evolved, which was very close to the predicted 0.5 mol per mol of epoxide consumed in Scheme 4and Equation (4). Hydrolysis of the titanium alkoxide product and characterization of the organic product confirmed that allylic alcohols 14 a and 14 b were formed in a5:1 ratio.…”
Section: Mystery 1: the Case Of The Vanishing Intermediatementioning
confidence: 99%
See 1 more Smart Citation
“…[22] Under catalytic conditions, Ti III species are mainly present as complex 3 in the presence of excess collindine•HCl (Scheme 1, a). [23] Cp 2 Ti III Cl can also be synthesized via electrochemical reduction of Cp 2 TiCl 2 . [24] Recently, a novel photogeneration of Cp 2 Ti III Cl with the aid of a photocatalyst was reported by the Gansäuer group and Shi group (Scheme 1, b).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The key to success was the formation of a stable complex A in reactions while decreasing the concentration of active Cp 2 Ti III Cl. 17,18 We were interested in the radical opening/cyclization reaction of epoxides which has attracted considerable attention from the synthetic community and has been used numerous times in the synthesis of natural products. 19,20 Nevertheless, this reaction required stoichiometric metallic reductants and proceeded slowly particularly with sterically hindered substrates even with high catalyst loading.…”
mentioning
confidence: 99%